2010
DOI: 10.1590/s0103-84782010000300010
|View full text |Cite
|
Sign up to set email alerts
|

Perfil proteico e metabolismo oxidativo de cordeiros experimentalmente infectados pelo Haemonchus contortus e suplementados com selênio e vitamina E

Abstract: Perfil proteico e metabolismo oxidativo de cordeiros experimentalmente infectados peloHaemonchus contortus e suplementados com selênio e vitamina E

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
1
3
0
3
Order By: Relevance
“…Different results were obtained by Nicolodi (2008) with selenium and vitamin E supplementation in sheep experimentally infected by H. contortus , and by Mattos et al. (2005) with such supplementation in goats naturally infected by H. contortus .…”
Section: Resultsmentioning
confidence: 93%
“…Different results were obtained by Nicolodi (2008) with selenium and vitamin E supplementation in sheep experimentally infected by H. contortus , and by Mattos et al. (2005) with such supplementation in goats naturally infected by H. contortus .…”
Section: Resultsmentioning
confidence: 93%
“…Zn and Cu are known to play an important role in the animal organism (Herdt and Hoff, 2011). In addition, some researchers have shown that the use of Cu and other minerals, such as nutritional supplements may help controlling the parasites (Nicolodi et al, 2010;Fausto, 2011). However, there is still lack of studies using the combination of minerals in an attempt to provide better conditions to face the severe parasitism caused by H. contortus.…”
Section: Introductionmentioning
confidence: 99%
“…Nicolodi et al (2010) relataram que não há influência da suplementação com selênio e vitamina E no perfil proteico e metabolismo oxidativo quando os cordeiros se encontram severamente parasitados por Haemonchus contortus.…”
Section: Resultsunclassified